2021
DOI: 10.1136/bmjopen-2020-045250
|View full text |Cite
|
Sign up to set email alerts
|

Family refusal of eye tissue donation from potential solid organ donors: a retrospective analysis of summary and free-text data from the UK National Health Service Blood and Transplant Services (NHS-BT) National Referral Centre (1 April 2014 to 31 March 2017)

Abstract: ObjectivesLong-standing undersupply of eye tissue exists both in the UK and globally, and the UK National Health Service Blood and Transplant Service (NHSBT) has called for further research exploring barriers to eye donation. This study aims to: (1) describe reported reasons for non-donation of eye tissue from solid organ donors in the UK between 1 April 2014 and 31 March 2017 and (2) discuss these findings with respect to existing theories relating to non-donation of eyes by family members.DesignSecondary ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Data from UK-based studies indicate that personal views of potential donors and family decision-makers are influential in triggering a decline to donate when ED is proposed. 4 Prominent concerns include potential for disfigurement, 5 beliefs compatible with eyes being needed in the afterlife and/or that eyes as 'windows to the soul' are an essential aspect of a person even after death. 5,6 ED is also known to elicit specific disgust-type responses in some patients and family members, characterised as an 'ick factor' attended by feelings of squeamishness in respondents 7 that is not observed in other forms of donation.…”
Section: The Unique and Specific Case Of Eye Donationmentioning
confidence: 99%
“…Data from UK-based studies indicate that personal views of potential donors and family decision-makers are influential in triggering a decline to donate when ED is proposed. 4 Prominent concerns include potential for disfigurement, 5 beliefs compatible with eyes being needed in the afterlife and/or that eyes as 'windows to the soul' are an essential aspect of a person even after death. 5,6 ED is also known to elicit specific disgust-type responses in some patients and family members, characterised as an 'ick factor' attended by feelings of squeamishness in respondents 7 that is not observed in other forms of donation.…”
Section: The Unique and Specific Case Of Eye Donationmentioning
confidence: 99%
“…Addressing barriers to ED require attention to the unique and specific challenges that are associated with this specific form of donation; for example, why do family members of organ donors frequently reject ED despite agreeing to other organs (and tissues)? Data from UK-based studies over the past five years indicate that personal views of potential donors and family decision makers are influential in triggering a decline when ED is proposed (Bracher et al 2021 ). Prominent concerns include potential for disfigurement (Lawlor and Kerridge 2011 ), beliefs compatible with eyes being needed in the afterlife, and/or that eyes as ‘windows to the soul’ are an essential aspect of a person even after death (Lawlor and Kerridge 2014 ).…”
Section: The Unique and Specific Case Of Eye Donation (Ed)mentioning
confidence: 99%
“…In 45% of countries which provide corneal tissue donation services, the system requires explicit consent from the donor and/or their family (opt-in) 1. Several studies worldwide have reported high rates of consent refusal2 3 with concern about the ‘ick factor’ (repulsion/disgust response) of ‘eye donation.’2 4…”
Section: Introductionmentioning
confidence: 99%